Eddy current loss behavior of hollow circular cylinder due to time-varying electromagnetic field - Balpande, Bhushan B.; Kedar, Ganesh D.; Matlam, J.L. (Zielona Góra: Uniwersytet Zielonogórski)
The purpose of this study is to investigate the effects of a time-varying electromagnetic field on the quasi-static thermoelastic behavior of a finitely conducting hollow circular cylinder. As a consequence of a time-varying electromagnetic field, conducting currents, also known as eddy currents, are induced inside the cylinder. We treat the Joule heat that the induced eddy currents generate due to resistive heating as a thermal loading of the cylinder.
Keywords: Joule heating; eddy current loss; skin effect; magneto-thermoelasticity; finite Hankel and Laplace transform; Marchi-Zgrablich transform